2021
DOI: 10.1021/acs.accounts.0c00702
|View full text |Cite
|
Sign up to set email alerts
|

Transformations Among Colloidal Semiconductor Magic-Size Clusters

Abstract: Conspectus A knowledge of colloidal semiconductor magic-size clusters (MSCs) is essential for understanding how fundamental properties evolve during transformations from individual molecules to semiconductor quantum dots (QDs). Compared to QDs, MSCs display much narrower optical absorption bands; the higher cluster stability gives rise to a narrower size distribution. During the production of binary QDs such as II–VI metal (M) chalcogenide (E) ones, binary ME MSCs observed were interpreted as side products and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
103
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(112 citation statements)
references
References 49 publications
9
103
0
Order By: Relevance
“…It is established that colloidal semiconductor compound magic-size clusters (MSCs) have particular precursor compounds (PCs). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is established that colloidal semiconductor compound magic-size clusters (MSCs) have particular precursor compounds (PCs). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Thef ormer (MSC-A) exhibits distinct optical absorption peaking at ac onstant wavelength A expressed in nanometers (nm), while the latter (PC-A) is usually transparent at this wavelength Aa nd to longer wavelengths.T he MSCs and their counterpart PCs are quasi isomers and transform mutually via reversible intramolecular reorganization. Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1). ForaMSC-A to MSC-B transformation, the three steps are MSC-A to PC-A, PC-A to PC-B,and PC-B to MSC-B.However,the reported transformations are limited to those between two binary MSCs, [3][4][5][6][7][8][9][10] or between ab inary MSC and at ernary MSC.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54][55] We anticipate that the PC-enabled pathway (Scheme 1) has general applicability for transformations such as from PL CdSe dMSC-460 to dMSC-513, [36] as well as from PL CdTedMSC-427 to dMSC-495, to dMSC-550, and to dMSC-600. [31] Thepresent findings bring sophisticated insight into the pathway of the MSC evolution and transformation, the latter of which experiences reactions of monomer substitution [1] or addition that transform two MSC counterpart PCs.…”
Section: Discussionmentioning
confidence: 90%
“…At sufficiently high concentrations (a and b), the fragmentation of PC-393 enabled the dMSC-393 to dMSC-460 transformation (Scheme 1). At low concentrations (c), the fragmentation of PC-393 facilitated the nucleation and growth of conventional QDs (Scheme S1) [1,2].…”
mentioning
confidence: 99%
“…Furthermore,t he transformation between types of MSCs has been observed, [1][2][3][4][5][6][7][8][9][10] following ap athway that appears to be PC-enabled comprising three key steps (Scheme S1). ForaMSC-A to MSC-B transformation, the three steps are MSC-A to PC-A, PC-A to PC-B,and PC-B to MSC-B.However,the reported transformations are limited to those between two binary MSCs, [3][4][5][6][7][8][9][10] or between ab inary MSC and at ernary MSC. [1,2,5] Before the present study, transformations in ternary MSCs have not been reported.…”
Section: Introductionmentioning
confidence: 99%